Clinical and Demographic Factors Associated With Receipt of Non Guideline-concordant Initial Therapy for Nonmetastatic Prostate Cancer. (February 2016) - Hamilton, Ann S.; Fleming, Steven T.; Wang, Dian; Goodman, Michael; Wu, Xiao-Cheng; Owen, Jean B.; Lo, Mary; Ho, Alex; Anderson, Roger T.; Thompson, Trevor
Abstract : Objectives: To determine the extent to which initial therapy for nonmetastatic prostate cancer was concordant with nationally recognized guidelines using supplemented cancer registry data and what factors were associated with receipt of nonguideline-concordant care. Methods: Initial therapy for 8229 nonmetastatic prostate cancer cases diagnosed in 2004 from cancer registries in 7 states was abstracted as part of the Centers for Disease Control's Patterns of Care Breast and Prostate Cancer study conducted during 2007 to 2009. The National Comprehensive Cancer Network clinical practice guidelines version 1.2002 was used as the standard of care based on recurrence risk group and life expectancy (LE). A multivariable model was used to determine risk factors associated with receipt of nonguideline-concordant care. Results: Nearly 80% with nonmetastatic prostate cancer received guideline-concordant care for initial therapy. Receipt of nonguideline-concordant care (including receiving either less aggressive therapy or more aggressive therapy than indicated) was related to older age, African American race/ethnicity, being unmarried, rural residence, and especially to being in the high recurrence risk group where receiving less aggressive therapy than indicated occurred more often than receiving more aggressive therapy (adjusted OR=4.2; 95% CL, 3.5-5.2 vs. low-risk group). Compared with life table estimates adjusted for comorbidity, physicians tended to underestimate LE. Conclusions: Receipt of less aggressive therapy than indicated among high-risk group men with >5-year LE based on life table estimates adjusted for comorbidity was a concern. Physicians may tend to underestimate 5-year survival among this group and should be alerted to the importance of recommending aggressive therapy when warranted. However, based on more recent guidelines, among those with low-risk disease, the proportion considered to be receiving less aggressive therapy than indicated may now be lower because active surveillance is now considered appropriate.